A pilot program of knowledge translation and implementation for newborn resuscitation using US Peace Corps Volunteers in rural Madagascar. Issue 1 (December 2016) - Close, Kristin; Karel, Michele; White, Michelle
Abstract Background Prevention of adverse perinatal outcome using the Helping Babies Breathe (HBB) neonatal resuscitation algorithm can reduce perinatal mortality in low income settings. Mercy Ships is a non-governmental organisation providing free healthcare education in sub-Saharan Africa and in an attempt to reach more rural areas of Madagascar with our neonatal resuscitation training we designed a novel approach in collaboration with US Peace Corps Volunteers (PCV). PCVs work in rural areas and contribute to locally determined public health initiatives. Method We used a model of knowledge translation and implementation to train non-medical PCVs in HBB who would then train rural healthcare workers. Bulb suction and a self-inflating bag were donated to each health centre. We evaluated knowledge translation and behaviour change at 4 months using the Kirkpatrick model of evaluation. Results Ten PCVs received training and then trained 42 healthcare workers in 10 rural health centres serving a combined population of over 1 million. Both PCVs and rural healthcare workers showed significant increases in knowledge and skills (p  < 0.001). The commonest behaviour changes persisting at 4 months were adequate preparation before delivery; use of rubbing and drying as a means of stimulation instead of foot tapping or back slapping; and use of the self-inflating bag to give respirations. Anecdotal evidence of changes in neonatal outcome were reported in several health care centres. Conclusion Our study demonstrates that non-medically trained PCVs can be used to successfully train rural healthcare workers in newborn resuscitation using the HBB algorithm and this results in improvements in personal and organizational practice at 4 months, including anecdotal evidence of improved patient outcome. Our novel method of training, including the provision of essential equipment, may be another tool in the armamentarium of those seeking to disseminate good practice to the most rural areas.